Potential role of miR-29b from mesenchymal stromal cell-derived extracellular vesicles in leukemic cell progression - Heejei Yoon; Silvia Park; Yong-Rim Kwon; Yoo-Jin Kim (PLoS ONE, 2025)
Crosstalk between leukemic cells and their surrounding mesenchymal stromal cells (MSCs) in the bone marrow microenvironment is crucial for the pathogenesis of myelodysplastic syndromes (MDS) and is mediated by extracellular vesicles (EVs). The EV-specific miRNAs derived from MDS-MSCs remain poorly explored. EVs isolated from HS-5, an immortalized stromal cell line, promoted the proliferation and 5-azacytidine (AZA) resistance of SKM-1 cells. EVs from MDS-MSCs and HS-5 cells showed significantly higher miRNA-29b-3p but lower let-7a-5p and miR-23-3p compared to healthy controls. miR-29b was selected for further investigation because it negatively regulates epigenetic modifier genes such as DNMTs and TETs, mutations of which are common in MDS. When we transduced miR-29b into leukemic cells, these cells demonstrated greater resistance to AZA and venetoclax than did their parental cells, mirroring the effect observed with HS-5 EVs. The introduction of miR-29b down-regulated DNMT1, DNMT3L, TET1, and TET2, which may underlie the changes in DNA methylation levels, increased chromosomal instability, activation of type I interferon pathways, acquired cell migration, and drug resistance observed in leukemic cells. Overall, we suggest that the sustained influx of miR-29b through EVs may catalyze the evolution of leukemic cells, and its clinical relevance warrants further investigation.